Death on the night of the lost lizards [large type] - Buckley, Julia, 1964- (A Hungarian tea house mystery, 2021)
"Hana Keller is getting ready for a lovely holiday season. When she receives a rare tea set as a birthday gift, she decides to host a tea at her apartment for her closest friends. During the cozy get-together, one of Hana's friends gets word that a murderer is on the loose. Hana soon learns that the victim was Sandor Balog, a professor of Hungarian Studies at the local college. With her growing psychic ability, Hana senses that she is going to be pulled into the investigation of the professor's death somehow. With her sexy boyfriend Erik on the case, Hana finds the Tea House steeped in suspects. She studies the smiling faces celebrating the season, but the real killer is good at hiding the truth and putting Hana in the hot seat"--